2023
DOI: 10.3390/ijms241713511
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Mesenchymal Stem Cells in Cancer Pathophysiology: Pro-Tumorigenic Effects versus Therapeutic Potential

Youssef Slama,
Franck Ah-Pine,
Mohamed Khettab
et al.

Abstract: Mesenchymal stem/stromal cells (MSCs) are multipotent cells involved in numerous physiological events, including organogenesis, the maintenance of tissue homeostasis, regeneration, or tissue repair. MSCs are increasingly recognized as playing a major, dual, and complex role in cancer pathophysiology through their ability to limit or promote tumor progression. Indeed, these cells are known to interact with the tumor microenvironment, modulate the behavior of tumor cells, influence their functions, and promote d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 350 publications
0
1
0
Order By: Relevance
“…On the other hand, it has also been found that MSCs may contribute to tumour growth by fostering a supporting tumour vascular network which modulates the peritumour immune environment, protecting it from immune attack, and promoting the proliferation and invasiveness of cancer stem cells [17][18][19][20][21] (Figure 1). This paradoxical behaviour of MSCs in tumours highlights the need for cautious and nuanced application in anti-cancer therapeutic approaches [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has also been found that MSCs may contribute to tumour growth by fostering a supporting tumour vascular network which modulates the peritumour immune environment, protecting it from immune attack, and promoting the proliferation and invasiveness of cancer stem cells [17][18][19][20][21] (Figure 1). This paradoxical behaviour of MSCs in tumours highlights the need for cautious and nuanced application in anti-cancer therapeutic approaches [22,23].…”
Section: Introductionmentioning
confidence: 99%